Approaches to forest site classification as an indicator of teak volume production - Santos, Mario Lima dos (2023)
We conducted a study on the dominant height growth of clonal teak (Tectona grandis Linn F.) plantations in the Brazilian Amazon to assess their potential and its agreement with volumetric production. We employed two approaches, ADA (algebraic difference) and GADA (generalized algebraic difference), and analyzed data from 58 permanent plots collected over a 10 year period. To classify the sites, we developed equations and evaluated their accuracy using various criteria, including correlation coefficient, mean square of residual, Akaike’s criterion, distribution of residuals, and validation through equivalence testing (TOST). We also assessed the biological realism of the constructed curves. We used cluster evaluation and dendrogram comparison to assess the agreement between site index and volumetric production for each approach. The Lundqvist–Korf baseline models (M1–ADA and M4–GADA) proved to be accurate and realistic in estimating dominant height in both approaches. Our findings indicate that the approaches utilizing dynamic equations and generating polymorphic curves effectively represent the sites and indicate the volumetric production of the plantations, with 98.3% of agreement rate. Based on our results, we recommend the use of ADA and GADA approaches for estimating the dominant height of clonal teak plantations in the Eastern Brazilian Amazon.